An expeditious synthesis of early transition metal carbide nanoparticles on graphitic carbons. Issue 61 (7th July 2016) - Ressnig, Debora; Moldovan, Simona; Ersen, Ovidiu; Beaunier, Patricia; Portehault, David; Sanchez, Clément; Carenco, Sophie
Abstract : Fast and furious: the reaction of potassium graphites with metal chloride is initiated at room temperature and proceeds expeditiously to yield supported crystalline metal carbide nanoparticles. Abstract : An expeditious synthesis of metal carbide nanoparticles onto various carbon supports is demonstrated. The procedure is versatile and readily yields TiC, VC, Mo2 C and W2 C nanoparticles on different types of carbons. The reaction is initiated at room temperature and proceeds within seconds. This novel synthetic route paves the way for a large variety of metal carbide–carbon nanocomposites that may be implemented in emerging nanotechnology fields.